MIGRATION AND RADICAL IDEOLOGIES: NURUDDIN FARAH’S NORTH OF DAWN (International Journal of Food and Nutritional Sciences, 2022)
The history of a nation affects the future of a nation for generations. After the end of colonial rule, Somalia witnessed the dictatorial rule of Siad Barre which is followed bydisastrouscivil war, violence, endless suffering and massive migration of Somalis to the neighboring nations and into different parts of the world. Nuruddin Farah, a major postcolonial Somalinovelist, in his thirteenth novel North of Dawn (2018) captures the violence, devastation, terrorism, and the effects of decades of civil war in Somalia. This paper will explore how thenovel North of Dawn brings out the horrific images of refugee camps, gender violence, and the existence of radical extremist religious ideologies in every religion, society and nation